Lyme Disease and Pregnancy - James M. Alexander; Susan M. Cox (Hindawi Limited, 1995)
Lyme disease is the most commonly transmitted vector-borne disease in the United States, with many regions of the country at risk. Like other spirochete-borne infections, Lyme disease progresses in stages, making diagnosis in the early stages of the illness and prompt treatment important for cure. An early diagnosis is made difficult by the less-than-ideal serologic tests and the varied clinical presentations of the disease. Although Lyme disease has been reported in pregnancy, the transmission rate to the fetus and potential harmful effects are largely unknown. This review discusses the diagnosis, clinical course, and treatment of Lyme disease with an emphasis on the pregnant patient.